Evaluation of some element and mineral levels in prescription and non-prescription dog diets - Or, Mehmet Erman (Slovenian veterinary research, 2024)
Various prescription diets prescribed by veterinarians for specific diseases in dogs have been developed and introduced to the market. Trace element and mineral levels, which are essential for healthy living conditions in animals, can differ in both pre-scription and non-prescription foods. In our study, it was aimed to determine the levels of some elements and minerals in various prescription and non-prescription dry foods used in dog nutrition and to evaluate their therapeutic importance.In the study, a total of 100 different prescription dry food formulated for hepatic dis-eases (H, n=25), renal diseases (R, n=25), gastrointestinal diseases (GI, n=25) and, al-lergic diseases (HA, n=25) were used. Non-prescription dry foods from different flavors and brands in the market were considered as the control group (C, n=50). Copper (Cu), Iron (Fe), Manganese (Mn), Zinc (Zn), Selenium (Se), Calcium (Ca), and Phosphorus (P) levels of all dry foods were analyzed by Inductively Coupled Plasma-Optical Emission Spectrometer (ICP-OES, Thermo iCAP 6000 series) and the results were compared be-tween groups. Statistical analysis was evaluated using SPSS 21.Cu levels in GI and HA groups were higher than in the control group (p<0.05 and p<0.01, respectively). Fe levels were higher in the GI group and lower in the HA group than in the control group (p<0.05). Mn level was significantly higher in the H group compared to the control group (p<0.001). The Mn levels in GI and HA groups were higher than the control group (p<0.01). There was no statistical difference in Se and Zn levels between prescription and non-prescription dry foods. Ca and P levels in all groups were statisti-cally lower than in the control group (p<0.001).There are significant differences in element and mineral levels in prescription and non-prescription dry foods. These values may be out of the legal limits determined by EU Regulation. Considering the therapeutic purpose of these prescription formulas, some element and mineral amounts were determined as inappropriate.
Keywords: dog; elements; food; minerals